Developing a service evaluation index for Internet addiction through the Delphi method. Issue 4 (8th August 2017) - Chun, JongSerl; Lee, Hae Kook
Abstract: This study was conducted to develop a service evaluation index for Internet addiction through expert consensus using the Delphi method in South Korea. The study contained three rounds: we drafted the index in the first round by reviewing the existing literature and seeking expert advice, and in rounds two and three, we consulted 12 experts via an online survey to gather their opinions on the appropriateness, clarity, and applicability of the drafted index. In rounds two and three, we collected more-detailed opinions based on the results of earlier rounds. Content validity was high, and it increased during the later rounds of the Delphi study. The Internet addiction service evaluation index that resulted comprised four categories: prevention, treatment, aftercare, and service outcomes. The prevention section contains 17 sub-indices, including preventive education, a screening test and intensive prevention programs, and service promotion. The treatment section contains 15 sub-indices that evaluate diagnosis, planning, and treatment services. The aftercare section uses two sub-indices to assess whether a systematic aftercare is provided. The service outcome section includes 19 sub-indices that evaluate service effectiveness, diagnosis of comorbid conditions, and risk factors. This index could effectively standardize services, facilitate operations, and promote objective evaluation within related service delivery systems.